SOCIAL WORK PRINCIPLES AND THE INTERFACE WITH THE CULTURE OF PEACE - Grossi, Patrícia Krieger; de Oliveira, Simone Barros; Grossi, Márcio Lima (European Scientific Journal, ESJ, 2014)
This article aims to unveil the interface of the culture of peace with social work´s principles. Social work´s principles are based on freedom, autonomy, equality, social justice, and respect for human rights. It envisions a society without any type of discrimination based on religion, race, social class, gender, age and ethnicity. Based on these principles, we can conclude that social workers are peace builders by nature, because of their ongoing commitment with overcoming oppressive realities and their constant pursuit of social justice.